(untitled) (Research, Society and Development, 2023)
The present research aims to analyze the medications used during the COVID-19 period for the treatment of the virus, as well as to analyze the sequelae left and their relationship with medications used to curb the proliferation of the virus. Thus, the adopted methodology is based on a bibliographical and descriptive research, elaborated through already published materials such as articles and periodicals, seeking answers without direct interference from the authors of this research. In addition to seeking to study the most used medications during the pandemic period, measuring whether or not there is interference with the consequences left by the virus. Despite the varied adverse reactions, the drugs in the so-called “Kit-COVID” often have reactions that aggravate heart problems, as well as episodes of headache and dizziness. In view of this, the performance of the pharmaceutical professional is of paramount importance, since pharmacists can apply their technical capacity to the maximum in the management of medicines and diseases, guidelines on self-medication, ensuring that it is done correctly and safely through the use of MIPs, as well as ensuring health promotion in the midst of the COVID-19 pandemic.